Mesenchymal stromal cell-derived membrane particles suppress kidney fibrosis - Shengbing Li; Ana Merino; Sander Korevaar; Thierry P. P. van den Bosch; Carla C. Baan; Marlies E. J. Reinders; Martin J. Hoogduijn (Stem Cell Research & Therapy)
Abstract Background Kidney injury, typically accompanied by inflammation, is a driver for kidney fibrosis, which contributes to the development of kidney failure. Mesenchymal stromal cells (MSC) have been proposed to have anti-fibrotic potential, but challenges such as their short persistence after infusion and inability to cross the lung capillary system due to their large size hamper their use for treatment of kidney fibrosis. It is hypothesized that the effects of MSC are partially dependent on phagocytosis of fragments of MSC by target cells and inhibiting excessive immune activation response. To exploit this effect of MSC, we developed nanosized membrane particles (MP) from MSC and explored their anti-fibrotic activity and immunomodulation effect in mouse and human kidney fibrosis models. Methods MP were generated from culture-expanded MSC through extrusion of isolated membranes. Unilateral kidney ischemia reperfusion injury (IRI) in male Balb/c mice was used to induce kidney fibrosis. MP generated from 1 × 106 MSC were injected in the tail vein immediately after anesthesia recovery. In a second model, human induced pluripotent stem cell-derived kidney organoids were exposed to 1% O2 for 48 h and 100 ng/mL IL-1β for 96 h to mimic IRI in vitro for inducing fibrosis. MP generated from 0.5 × 106 MSC were added to the medium for 4 consecutive days. Fibrosis and immune cell markers were subsequently measured. Results IRI induced the expression of transforming growth factor beta (TGFβ) and collagen type I alpha 1(COL1A1) in mouse kidneys. MP treatment significantly reduced TGF-β mRNA at day 3 while COL1A1 mRNA and protein were downregulated at day 7. We found no evidence for an immunomodulatory effect of MP, as the number and activity of infiltrating T cells and macrophages did not change. In kidney organoids, a rise in COL1A1 and TGF-β demonstrated successful fibrosis induction by hypoxia and IL-1β. MP significantly decreased these fibrosis markers. Additionally, immunohistochemistry revealed a reduction in the myofibroblast marker alpha smooth muscle actin. Conclusions Our results demonstrate that MP have anti-fibrotic properties in mouse kidney IRI and human kidney organoid models. These results indicate that MP have potential for the development of kidney fibrosis-inhibiting therapy.